Antinomia existente entre el reglamento para la conciliación en asuntos relacionados con infracciones de tránsito y el Código Orgánico Integral Penal - Pérez Flores, Doris Samantha (2022)
In Ecuador there are several problems related to the analysis of the normative practice in the administration of justice, since there are events in traffic matters that give way to a possible criminal proceeding, which must be previously investigated. Thus, the subject of investigation covers the conciliation in traffic matters, in relation to the extinction of the criminal action that is raised in the legal norm (Organic Integral Penal Code), therefore, there are norms at the end where a conflict between infraconstitutional norms is observed; Given the existence of the conflict, the so-called antinomy arises, so that if the process follows the provisions of the Regulations for conciliation in matters related to traffic offenses, the direct procedure must be developed, i.e., to make the conciliation effective, all phases of the process must be exhausted, with a sentence being fixed by the judge, which violates the basic guarantees of due process and the principles of procedural law.